Supervisory practices of elementary school principals in school health education in the Division of Quezon City, 1967-1968 - Perez, Encarnacion Quimpo 1920- (1970)
The aim of the study is to find out the extent to which certain supervisory practices in relation to the school health education program are carried out by the principals in the elementary grades in the Division of Quezon City. It seeks to know what phase of the school health education program received most attention, and the phase that received the least attention, from the principals in their supervision of the school health education program as perceived by the principals, district supervisors, and teachers.